Incidence of left vertebral artery origin directly from the aortic arch - Paunkoska, Anamarija; Dodevski, Ace (Faculty of Medicine, University Ss. Cyril and Methodius in Skopje, 2023)
The vertebral artery (a. vertebralis, VA) is classically described as the first branch of the ipsilateralsubclavian artery (a. subclavia).This study aimed to show the aberrant pattern of a. vertebralis sinistra.The study included 1000 CTA images taken from 1000 patients. The only recorded variation in the origin of a. vertebraliswas a separate origin of a. vertebralissinistra(LVA) in 28 of thepatients (2.8%). It was present as a four-vessel aortic arch pattern with a. vertebralissinistraarising between a. carotis communis sinistra(LCCA) and a. subclavia sinistra(LSA). Establishing the diagnosis of these variations is very important before cerebral angiography or endovascular surgeries in the head and neck region are performed.
Keywords: vertebral artery; origin; variations